THE IMPACT OF TRANSJAKARTA BUS RAPID TRANSIT ON LAND VALUE OF DKI JAKARTA PROVINCE SUBDISTRICTS - Rusadhi, Elin Pike (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2019)
To immediately curb severe traffic congestion, some cities choose to establish bus rapid transit (BRT) infrastructure over rail-transit. New establishment of transportation infrastructure should be followed by the increases of land value. This study mainly intents to determine the impact of TransJakarta BRT on land value of sub-districts in DKI Jakarta Province. There are two treatments in this thesis. This study utilizes difference-in-difference approach as well as score matching estimation namely Nearest Neighbor Matching (NNM). The research found that the new installation of BRT causes land value to increase around 20 – 30 percent. Hence it is correct to say that BRT impact on land value is on par with other transportation establishment such as railway. Its apparent benefit to land value can be used as basis to encourage more private and public-sector involvement in helping to fund the BRT installation.